1987
DOI: 10.1111/j.1398-9995.1987.tb00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil cationic protein and myeloperoxidase in nasal secretion as markers of inflammation in allergic rhinitis

Abstract: The inflammatory component of allergic rhinitis was studied by measuring the concentration and content of eosinophil cationic protein (ECP, specific for eosinophils) and myeloperoxidase (MPO, specific for neutrophils) in samples of nasal secretion from 20 pollen-allergic subjects. All secretion samples contained measurable concentrations of both proteins. The mean ECP concentrations on two occasions without pollen exposure were 950 and 1170 micrograms/l. The ECP concentration during the pollen season without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
2

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 18 publications
(16 reference statements)
2
44
2
Order By: Relevance
“…ECP is considered a useful parameter of eosinophil activation, as it is increased in serum biologic fluids of patients with allergic diseases [29], and provides a reliable indication of the severity of asthma and/or rhinitis [25, 26, 31, 32]. Our data seem to indicate that the presence of SAE IgE in serum may be linked to the clinical severity of patients allergic to HDMs.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…ECP is considered a useful parameter of eosinophil activation, as it is increased in serum biologic fluids of patients with allergic diseases [29], and provides a reliable indication of the severity of asthma and/or rhinitis [25, 26, 31, 32]. Our data seem to indicate that the presence of SAE IgE in serum may be linked to the clinical severity of patients allergic to HDMs.…”
Section: Discussionmentioning
confidence: 64%
“…Oehling et al [22]demonstrated IgE-dependent potentiation of histamine release against D. pteronyssinus extract with bacterial antigens in bronchial asthma. In addition, recent data suggest that SAEs have profound effects on human eosinophils, in terms of eosinophil apoptosis inhibition and cell surface antigen expression modulation [31]. Moreover, the involvement of eosinophil was previously demonstrated [23, 33, 34]in terms of IL-5, eotaxin and cysteinyl leukotriene production in polyp samples from patients suffering from asthma and/or aspirin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that activated eosinophils are involved in NP [33, 34]. Accordingly, ECP levels were increased in nasal lavage fluids and were also correlated with the symptom score, unlike eosinophil counts.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, antibodies to MBP have been used to localize eosinophils and to detect eosinophil degranulation in tissues from patients with diseases such as asthma [4], atopic dermatitis [25], vernal keratoconjunctivitis [26], and urticaria [14]. EDN and ECP have been regarded as eosinophil specific granule proteins, and assays for EDN and ECP have been used to monitor the role of eosinophils in allergic rhinitis [27][28][29][30], asthma [31][32][33][34], IgE-mediated late-phase cutaneous reactions [13], celiac and Crohn's diseases [35], idiopathic pulmonary fibrosis [36], and atopic dermatitis [37].…”
Section: Discussionmentioning
confidence: 99%